Editor's Choice – Covered vs. Bare Metal Stents in the Reconstruction of the Aortic Bifurcation: Early and Midterm Outcomes from the COBRA European Multicentre Registry. (May 2022) - Saratzis, Athanasios; Argyriou, Angeliki; Davies, Robert; Bisdas, Theodosios; Chaudhuri, Arindam; Torsello, Giovanni; Stavroulakis, Konstantinos; Zayed, Hany; ,; Abisi, Said; Coscas, Raphael; Dey, Ramita; et al.
Abstract : Objective: To report outcomes following endovascular revascularisation for severe aorto-iliac occlusive disease (AIOD) using covered (CS) or bare metal (BMS) stent(s). Methods: This was a retrospective cohort study including patients who underwent treatment with CS or BMS for AIOD between November 2012 and March 2020 in 12 European centres. Outcome measures included death, freedom from target lesion revascularisation (TLR), major amputation, and major adverse cardiac and cerebrovascular events (MACCE). Results: Overall, 252 patients (53% males; mean age 65 ± 10 years) were included (102 with a bare metal and 150 with a covered aortic stent); 122 (48%) presented with chronic limb threatening ischaemia (CLTI). Severe arterial calcification was noted in > 65% of patients, 70% presented with Trans-Atlantic Societies Consensus (TASC) D lesions, 32% and 46% had aortic or iliac chronic total occlusion (CTO), respectively. Median follow up was 17 months (range 6 – 40; none lost to follow up). Median inpatient stay was two days (range two to four). During the first 30 days, two patients died (both with covered aortic stents, because of cardiovascular events), none required TLR, two (1%) patients had a major amputation (all presented with CLTI), and three (1%) had a MACCE. At 17 months, mortality (BMS 14% vs. CS 7%, hazard ratio [HR] 0.97, 95% confidence interval [CI] 0.42 – 2.26, p  = .94, log rank test) and TLR (11% vs. 10%, HR 1.98, 95% CI 0.89 – 4.43, p  = .095) did not differ statistically significantly between the two groups; only three patients had a major limb amputation during late follow up (all with a covered stent). In a multivariable model, the use of an aortic CS did not influence TLR. In a conditional Cox regression, however, the concomitant use of aortic and iliac CSs was associated with improved freedom from TLR. Conclusion: Endovascular reconstruction with aortic CSs or BMSs for severe AIOD showed comparable midterm performance. The use of both aortic and iliac CSs seems to be associated with reduced TLR.